1999
DOI: 10.1002/(sici)1097-4644(19990915)74:4<616::aid-jcb11>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of osteoprogenitor proliferation and osteoblast differentiation in vitro

Abstract: Fetal rat calvaria cells plated at very low density generate discrete colonies, some of which are bone colonies (nodules) from individual osteoprogenitors that divide and differentiate. We have analyzed the relationship between cell proliferation and acquisition of tissue-specific differentiation markers in bone colonies followed individually from the original single cell to the fully mineralized state. The size distribution of fully formed nodules is unimodal, suggesting that the coupling between proliferatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
122
1
4

Year Published

2000
2000
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 257 publications
(140 citation statements)
references
References 30 publications
13
122
1
4
Order By: Relevance
“…A combination of limiting dilution single colony assays and replica plating is a useful technique to trap cells at definable developmental stages [24], [25]. In spite of the possibility of a gradient in the proliferation-differentiation sequence from the periphery to the center of developing bone colonies [31], the uniform ALP staining we saw in colonies selected here and the lack of a relationship between the colony size (not shown) and their developmental stage suggest that a development gradient, if present under our culture conditions, was restricted to a narrow range. Using this approach, we found a statistically significant difference in the adipogenic potential amongst colonies defined as being at three development stages: immature, intermediate and mature, but adipocytes were found in all three.…”
Section: Discussionmentioning
confidence: 76%
“…A combination of limiting dilution single colony assays and replica plating is a useful technique to trap cells at definable developmental stages [24], [25]. In spite of the possibility of a gradient in the proliferation-differentiation sequence from the periphery to the center of developing bone colonies [31], the uniform ALP staining we saw in colonies selected here and the lack of a relationship between the colony size (not shown) and their developmental stage suggest that a development gradient, if present under our culture conditions, was restricted to a narrow range. Using this approach, we found a statistically significant difference in the adipogenic potential amongst colonies defined as being at three development stages: immature, intermediate and mature, but adipocytes were found in all three.…”
Section: Discussionmentioning
confidence: 76%
“…The cells were not fully adhered until day 7, when they showed the characteristic flattened polygonal shape and they were metabolically active, displaying higher values of proliferation. It has been demonstrated that levels of Ca concentrations up to 300 mg/L are cytotoxic [25], but lower concentrations are suitable for cell proliferation, differentiation, and extracellular matrix mineralization. The new biomaterial obtained, Nurse’s A-phase, has a high proportion of CaO in its composition, causing the high level of Ca 2+ ion release in the first week.…”
Section: Discussionmentioning
confidence: 99%
“…The process of osteoblast differentiation is under various central and local controls including bone morphogenetic proteins (BMP), Indian hedgehog, fibroblast growth factor-2 (FGF2), Wnt, parathyroid hormone, and leptin [69]. Further, studies have proposed several possible mechanisms governing bisphosphonate-mediated osteoblast differentiation [10, 11].…”
Section: Introductionmentioning
confidence: 99%